Using Advanced Artificial Intelligence Technologies to Improve Institutional Performance in Business Associations in Riyadh - Almutairi, Mona Jeza; Alhallafi, Hassan Khidhr; Alabbas, Almotasim Khalil (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to analyze the impact of advanced artificial intelligence technologies on improving institutional performance in business associations in Riyadh, with a focus on measuring operational efficiency improvements, administrative decision quality, and identifying associated ethical and regulatory challenges. The research adopted a descriptive-analytical methodology, analyzing five previous studies published between 2021 and 2025 across various sectors. The study employed qualitative analysis tools to extract common patterns and key conclusions. The results showed that AI technologies significantly contributed to improving operational efficiency through task automation and enhanced administrative decision quality via advanced predictive analytics. The findings also revealed major challenges such as algorithmic bias, weak technological infrastructure, and lack of regulatory frameworks. The study recommended the necessity of developing a comprehensive strategic framework for adopting these technologies, with emphasis on enhancing ethical transparency, training human resources, developing digital infrastructure, and conducting more field studies to measure the actual impact of various applications.
Keywords: Technologies; Advanced Artificial Intelligence; Institutional Performance